Yacon (Smallanthus sonchifolius) Leaf Extract Attenuates Hyperglycemia and Skeletal Muscle Oxidative Stress and Inflammation in Diabetic Rats - Dos Santos, Klinsmann Carolo [UNESP]; Bueno, Bianca Guerra [UNESP]; Pereira, Luana Ferreira [UNESP]; Francisqueti, Fabiane Valentini [UNESP]; Braz, Mariana Gobbo [UNESP]; Bincoleto, Lahis Fernandes [UNESP]; Da Silva, Lilian Xavier [UNESP]; Ferreira, Ana Lúcia A. [UNESP]; De Melo Stevanato Nakamune, Ana Cláudia [UNESP]; Chen, C.-Y. Oliver; Blumberg, Jeffrey B.; Corrêa, Camila Renata [UNESP] (Wiley, 2017)
The effects of hydroethanolic extract of Yacon leaves (HEYL) on antioxidant, glycemic, and inflammatory biomarkers were tested in diabetic rats. Outcome parameters included glucose, insulin, interleukin-6 (IL-6), and hydrophilic antioxidant capacity (HAC) in serum and IL-6, HAC, malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) in soleus. The rats (10/group) were divided as follows: C, controls; C + Y, HEYL treated; DM, diabetic controls; and DM + Y, diabetic rats treated with HEYL. Diabetes mellitus was induced by administration of streptozotocin. C + Y and DM + Y groups received 100 mg/kg HEYL daily via gavage for 30 d. Hyperglycemia was improved in the DM + Y versus DM group. Insulin was reduced in DM versus C group. DM rats had higher IL-6 and MDA and lower HAC in the soleus muscle. HEYL treatment decreased IL-6 and MDA and increased HAC in DM rats. DM + Y rats had the highest CAT activity versus the other groups; GPx was higher in C + Y and DM + Y versus their respective controls. The apparent benefit of HEYL may be mediated via improving glucoregulation and ameliorating oxidative stress and inflammation, particularly in diabetic rats.